Telehealth during the COVID-19 pandemic regarding children with plano-valgus foot after subtalar arthroereisis - Kamila Pardus; Krystyna Stencel-Gabriel; Zbigniew Pilecki; Marcin Hajzyk (Kazimierz Wielki University, 2024)
Introduction: The COVID-19 pandemic brought about numerous changes. Access to health services was limited, and restrictions were imposed to prevent the spread of the disease. Consequently physical activity of children was limited due to their increased time at home, which could result in reduced physical performance and abnormal development. Aim: This study aimed to assess the access to physiotherapy and the use of telemedicine regarding children after subtalar arthroereisis surgery during the COVID-19 pandemic. Material and methods: Seventy-nine parents/guardians of children who underwent subtalar arthroereisis surgery at Chorzow Municipal Hospital Complex between May 2019 and May 2021 participated in the study. A self-administered questionnaire designed for the study was used as the research method. Results: The results showed that some respondents perceived the wait times at the National Health Service and the cost of private services as problems during the COVID-19 pandemic. However, increased problems associated with general access or course of treatment were not confirmed. Sixty-seven percent of respondents confirmed decreased physical activity in children due to the COVID-19 pandemic. One-third of parents noticed weight gain and muscle weakness in their children, while for 56% of respondents, the weight gain was not noticeable. In addition, more than 70% of the children had no complaints of pain. The results also showed that only 36.8% of respondents used telemedicine during the pandemic. Conclusions: The constraints imposed by the COVID-19 pandemic caused a decline in children's physical activity; one-third of parents reported weight gain in their children. In addition, waiting times for physiotherapy reimbursed by the National Health Fund were long, and the cost of private physiotherapy was higher; it could not be confirmed whether more patients subsequently used telemedicine.